Insiders And Outsiders: A Comparative Study Of The Political Debates On The Facebook Pages Of Party Leaders During Two Danish Election Campaigns - Schwartz, Sander; Rossi, Luca (AoIR Selected Papers of Internet Research, 2017)
This paper is a comparative content analysis of the political positions and debates in the Facebook comment sections of four Danish party leaders, examined during the two general election campaigns of 2011 and 2015. In the study we examine how the comments are distributed according to a predefined coding scheme of four positions ranging from support, intra-contestation, inter-contestation and smear. This coding scheme demonstrates how comments are distributed according to political position of insiders and outsiders, and whether a comment is related to a political issues. Our study finds that by far the most comments are supportive of the overall political agenda of the politician, with a smaller group of comments that are discussing politics, but within the overall political agenda of the politician. Even though the picture is the same for all four politicians, there are some notable differences between the profiles. However, it is clear that the Facebook comments in this study are primarily supportive comments with no political content, and then secondly a smaller group of comments related to political issue but within the overall political agenda of the politician. This seems to suggest that the comment threats are mostly used by loyal supporters and some critical insiders, but not clearly a space for critical debates between insiders and outsiders in relation to the political position associated with the politician.